Foliar water uptake in Pinus species depends on needle age and stomatal wax structures. (24th November 2022) - Roth-Nebelsick, Anita; Hacke, Uwe G; Voigt, Dagmar; Schreiber, Stefan G; Krause, Matthias
Abstract: Background and aims: Foliar water uptake (FWU) has been documented in many species and is increasingly recognized as a non-trivial factor in plant–water relationships. However, it remains unknown whether FWU is a widespread phenomenon in Pinus species, and how it may relate to needle traits such as the form and structure of stomatal wax plugs. In this contribution, these questions were addressed by studying FWU in current-year and 1-year-old needles of seven Pinus species. Methods: We monitored FWU gravimetrically and analysed the needle surface via cryo-scanning electron microscopy. Additionally, we considered the effect of artificial wax erosion by application of the surfactant Triton X-100, which is able to alter wax crystals. Key results: The results show for all species that (1) FWU occurred, (2) FWU is higher in old needles compared to young needles and (3) there is substantial erosion of stomatal wax plugs in old needles. FWU was highest in Pinus canariensis, which has a thin stomatal wax plug. Surfactant treatment enhanced FWU. Conclusions: The results of this study provide evidence for (1) widespread FWU in Pinus, (2) the influence of stomatal wax plugs on FWU and (3) age-related needle surface erosion.